2021
DOI: 10.3389/fcimb.2021.672472
|View full text |Cite
|
Sign up to set email alerts
|

P2x7 Receptor Signaling Blockade Reduces Lung Inflammation and Necrosis During Severe Experimental Tuberculosis

Abstract: The risk of developing severe forms of tuberculosis has increased by the acquired immunodeficiency syndrome (AIDS) epidemic, lack of effective drugs to eliminate latent infection and the emergence of drug-resistant mycobacterial strains. Excessive inflammatory response and tissue damage associated with severe tuberculosis contribute to poor outcome of the disease. Our previous studies using mice deficient in the ATP-gated ionotropic P2X7 receptor suggested this molecule as a promising target for host-directed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…P2RX7 is a low affinity eATP receptor (Di Virgilio et al, 2017), therefore its action has been associated with eATP accumulation induced by tissue cell death during infections (Amaral et al, 2014;Borges da Silva et al, 2020;Di Virgilio et al, 2017). Multiple immune cells and lung epithelial cells express P2RX7, and our group has previously shown that pharmacological P2RX7 inhibition led to decreased CD4 + T cell numbers in the lung parenchyma in response to MP287 (Santiago-Carvalho et al, 2021). Our results expand these findings by identifying that the infection-induced accumulation of lung parenchymal CD4 + T cells depends on P2RX7 signaling directly on T cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…P2RX7 is a low affinity eATP receptor (Di Virgilio et al, 2017), therefore its action has been associated with eATP accumulation induced by tissue cell death during infections (Amaral et al, 2014;Borges da Silva et al, 2020;Di Virgilio et al, 2017). Multiple immune cells and lung epithelial cells express P2RX7, and our group has previously shown that pharmacological P2RX7 inhibition led to decreased CD4 + T cell numbers in the lung parenchyma in response to MP287 (Santiago-Carvalho et al, 2021). Our results expand these findings by identifying that the infection-induced accumulation of lung parenchymal CD4 + T cells depends on P2RX7 signaling directly on T cells.…”
Section: Discussionmentioning
confidence: 98%
“…Whether P2RX7 serves as a microenvironmental sensor for lung CD4 + T cell accumulation, and whether P2RX7-expressing CD4 + T cells are the main promoter of lung damage rather than other cell types is not understood. Of note, we have found that, in correlation with protection from disease, transient P2RX7 blockade led to reduced numbers of CD69 + lung-parenchymal CD4 + T cells (Santiago-Carvalho et al, 2021). Moreover, P2RX7 is known to play an important role in the establishment of tissueresident memory (T RM ) CD8 + T cells in response to systemic viruses (Borges da Silva et al, 2018;Borges da Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…The selectively P2X7 antagonist was proven to significantly inhibit the innate immune cells and upregulate the immunosuppressive-associated T cells, indicating that this antagonist may be a kind of potential treatment[ 175 ]. The effect of P2X7-blockade drug has also been demonstrated in the mouse models with advanced tuberculosis[ 176 ]. In addition to the above intracellular signaling pathways (MAPK pathway), previous studies verified that P2X7R also regulated MyD88/NF-κB and PI3K/Akt/mTOR signaling pathways in innate and adaptive immune responses, which suggested that the key proteins in these pathways can be considered as novel therapeutic targets[ 177 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of P2X7R signalling can also lead to antimycobacterial activities. For instance, P2X7R inhibition with Brilliant blue G (BBG) can prevent the development of a severe form of Micobacterium tuberculosis -driven tuberculosis in mice with experimental advanced pulmonary tuberculosis [ 110 ], while the adoptive transfer of P2X7R KO hematopoietic cells in mice can lead to a reduced pneumonia as well as a lower lung Micobacterium bovis burden in comparison with WT mice [ 95 ]. Furthermore, P2X7R has been reported to be implicated during the Gram-positive bacterial infection responsible for sepsis .…”
Section: P2x7 Receptor Activation In Inflammationmentioning
confidence: 99%